2019
DOI: 10.1021/acsami.8b21592
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliated Black Phosphorus Promotes in Vitro Bone Regeneration and Suppresses Osteosarcoma Progression through Cancer-Related Inflammation Inhibition

Abstract: Nowadays chemotherapy is the main treatment for osteosarcoma disease, even if limited by the lack of selectivity between healthy and cancer cells during the inhibition of cell division. Herein, we propose the use of few-layer two-dimensional black phosphorous (2D bP) as an alternative tool for osteosarcoma treatment and report how 2D bP can stimulate newly forming bone tissue generation after osteosarcoma resection. In our study, we have developed an in vitro model to evaluate the efficacy of 2D bP material wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 36 publications
1
49
0
Order By: Relevance
“…Recently, many efforts have demonstrated that novel degradable 2D nanomaterials especially nanoclay particles and black phosphorus (BP) nanosheets with excellent bioactivity could induce osteogenic differentiation of stem cells . The innate osteoinductive performance of nanoclay were attributed to both biophysical properties (size, physical shape, and surface charge) and biochemical signaling (mineral ions dissolution products) of the nanomaterials, whereas the remarkable osteoinduction capability of BP were mainly mediated by in situ phosphorus driven, calcium‐extracted mineralized extracellular matrix during the process of BP degradation . Indeed, phosphorus is an essential element constituting about 1% of total body weight in humans, primarily as a constituent of bone .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many efforts have demonstrated that novel degradable 2D nanomaterials especially nanoclay particles and black phosphorus (BP) nanosheets with excellent bioactivity could induce osteogenic differentiation of stem cells . The innate osteoinductive performance of nanoclay were attributed to both biophysical properties (size, physical shape, and surface charge) and biochemical signaling (mineral ions dissolution products) of the nanomaterials, whereas the remarkable osteoinduction capability of BP were mainly mediated by in situ phosphorus driven, calcium‐extracted mineralized extracellular matrix during the process of BP degradation . Indeed, phosphorus is an essential element constituting about 1% of total body weight in humans, primarily as a constituent of bone .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have shown that tumor-associated inflammation, which is the seventh feature of cancer, is involved in every step of tumorigenesis and cancer progression [15][16]. were significantly associated with decreased OS in locally advanced or metastatic PC [18].…”
mentioning
confidence: 99%
“…The unique geometric and electronic structure of nano‐BP endows them many appealing surface properties and photoelectric properties that show great promising in biomedical and biosensing applications . Within every layer of BP with honeycomb structure, each phosphorus atom forms three covalent bonds with the adjacent phosphorus atoms, leaving one pair of electrons exposed outside.…”
Section: Nano‐bp Functionalizationmentioning
confidence: 99%